2022
DOI: 10.3390/foods11162445
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Influence of Lactic Acid Bacteria Fermentation on the Variations in Flavor of Chickpea Milk

Abstract: This study aimed to evaluate the influence of fermentation on the levels of free amino acids (FAAs) and variations of volatile odorants in four groups of chickpea milk. Electronic nose (E-nose) and gas chromatography–mass spectrometry (GC-MS) data were subjected to mutual validation. W2S and W3S sensors of E-nose were sensitive to volatile constituents in the four groups of unfermented and fermented specimens. After fermentation, the levels of FAAs in the four groups of specimens decreased to varying degrees. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…1 A). It was found that the number of viable bacteria of L. plantarum Y2 in the fermentation broth was directly proportional to the fermentation time and gradually decreased after 24 h, due to the reduced metabolic capacity of the system in the late stages of fermentation and the threatening effect of the lower pH on the reproduction of L. plantarum [31] . The number of viable bacteria in all sonicated groups in the logarithmic and stable phases was higher than that in the non-sonicated group, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 A). It was found that the number of viable bacteria of L. plantarum Y2 in the fermentation broth was directly proportional to the fermentation time and gradually decreased after 24 h, due to the reduced metabolic capacity of the system in the late stages of fermentation and the threatening effect of the lower pH on the reproduction of L. plantarum [31] . The number of viable bacteria in all sonicated groups in the logarithmic and stable phases was higher than that in the non-sonicated group, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Acetoin (E2) improves the overall sensory acceptability of fermented soymilk ( 65 ). Due to carbonyl compounds could be converted by lactic acid bacterial metabolism into further well-known odor substances, like ketones, esters, or organic acids ( 66 ). So, post-fermentation, the good aroma substance increased in LPFJ, while the beany flavor weakened, improving the total flavor of the beverage.…”
Section: Resultsmentioning
confidence: 99%
“…PCA was an important dimensionality reduction method used in data processing (Zhang et al, 2022). A biplot of the PCA for the phenolic profiles detected in the blueberry juice after fermentation was exhibited in Figure 1.…”
Section: Differences In Phenolics Profiles After Fermentationmentioning
confidence: 99%